Frenzy - Cooper, Ian (Freelance writer) (Auteur, 2018)
Frenzy is perhaps Hitchcock's most nakedly autobiographical film, representing both a comeback and farewell to the city of his birth. Ian Cooper discusses the evolution of the film, its production, reception, and place in Hitchcock's oeuvre, as well as its status as a key film of ""sleazy Seventies"" British cinema.
Keywords: Frenzy (Motion picture); Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation.; Hitchcock, Alfred, -- 1899-1980; Criticism, interpretation, etc.